as verify the following
(a) (-22)x(-4)+(-5)] = [[-22] XF 4)] + [(-22)x(-5))
Answers
Answered by
0
Step-by-step explanation:
(−22)×((−4)+(−5))=((−22)×(−4))+(−22)×(−5))
(−22)×(−4−5)=88+110
−22×(−9)=198
198=198
therefore.
LHS=RHS...proved...
I HOPE IT WILL HELP YOU
Answered by
0
Answer:
(-22)x(-4)+(-5)=[[-22]XF 4]+[(-22)x(-5)
Step-by-step explanation:
(-22)x(-9)=88+110
198=198
LHS=RHS
Similar questions
Chemistry,
2 months ago
Math,
4 months ago
Hindi,
11 months ago
Computer Science,
11 months ago
Science,
11 months ago